Polystyrene Nanofiber Materials for Visible-Light-Driven Dual Antibacterial Action via Simultaneous Photogeneration of NO and O2((1)Δg) - Dolanský, Jiří; Henke, Petr; Kubát, Pavel; Fraix, Aurore; Sortino, Salvatore; Mosinger, Jiří (ACS applied materials & interfaces, 2015)
This contribution reports on the preparation, characterization, and biological evaluation of electrospun polystyrene nanofiber materials engineered with a covalently grafted NO photodonor and ionically entangled tetracationic porphyrin and phthalocyanine photosensitizers. These photofunctional materials exhibit an effective and simultaneous photogeneration of two antibacterial species such as nitric oxide (NO) and singlet oxygen, O2((1)Δg) under illumination with visible light, as demonstrated by their direct detection using amperometric and time-resolved spectroscopic techniques. Dual-mode photoantibacterial action is demonstrated by antibacterial tests carried out on Escherichia coli.
Keywords: Ion Exchange; iontová výměna; Anti-Bacterial Agents; Polystyrenes; spektroskopie infračervená s Fourierovou transformací; singlet oxygen; Light; nitric oxide; Fluorescence; Solutions; světlo; Spectrophotometry, Ultraviolet; roztoky; fluorescence; antibacterial; photogeneration; kyslík; Spectroscopy, Fourier Transform Infrared; elektrochemické techniky; oxid dusnatý; nanovlákna; Nitric Oxide; antibakteriální látky; Electrochemical Techniques; nanofiber; Nanofibers; Oxygen; spektrofotometrie ultrafialová; polystyreny